Plenty / David Hare - Hare, David, 1947- (Faber & Faber, 2016)
Drama counterpointing experiences of English-woman helping the French Resistance during World War II with her life in the following twenty years. Music, 12 scenes, 9 men, 5 women, 4 interiors, 2 exteriors.